Causes and Recommendations for Controlling Coal Damage When Blasting Overburden - R Frank' Mammele Chiappetta; Conny Postupack (International Society of Explosives Engineers, 1988)
A major problem that has continued to plague the surface coal industry is blast induced damage to the coal seam. Atlas Powder Company has addressed this situation through seven years of field research in full-scale production environments. Many operations across the United States have been evaluated.